2011 IEEE 61st Electronic Components and Technology Conference (ECTC) 2011
DOI: 10.1109/ectc.2011.5898802
|View full text |Cite
|
Sign up to set email alerts
|

Impact of board configuration and shock loading conditions for board level drop test

Abstract: An effort has been made in this study to evaluate the dynamics and characteristics of the test vehicle in a board level drop test. A thorough understanding of the behavior of the test vehicle is examined by characterizing its response under different test profiles and board dimensions. This is done in an attempt to optimize the test procedure used to qualify electronic products subjected to high strain rate drop/shock environment.The effects of peak acceleration and change in velocity of the impact pulse on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…1c and 1d will result in uniform strains and stresses across all components which would make the test much more efficient and data analysis much easier. This has been partially verified by P. Guruprasad et al [8] as shown in Fig. 1e.…”
Section: Introductionsupporting
confidence: 74%
“…1c and 1d will result in uniform strains and stresses across all components which would make the test much more efficient and data analysis much easier. This has been partially verified by P. Guruprasad et al [8] as shown in Fig. 1e.…”
Section: Introductionsupporting
confidence: 74%